The Beginnings of Urbanization & the Transformations of the Desert Family Structure: from the Family Home to the 'Independent' houses - عطية , قصي (Milev Journal of Research and Studies, 2020)
The totality of the transformations taking place in The City of Ouargla through its implicit manifestations and cultural ramifications, has a clear impact on the structure of extended families as an inevitable product of urban behavior and its cultural and economic reflection on the manifestations of traditional social lifestyles of individuals and groups, and their quest to rebuild value models in their new social relationships as a temporary response to the mechanisms of urbanization and integration, this dynamic process that actors in the urban space of the oasis, it opens the door to many questions that we must quickly answer based on the approaches of urban anthropology and symbolic interactive , which has established a deeper dimension in our analysis of the discourse of actors, and researchers, with different ethnic affiliations and multi-ethnic ideological backgrounds , due to the complex strategies of the modern urban fabric practiced by social groups in their possession of desert spaces, in many different central intersections of both local and urban bedouins through their cultural and field discourses